Polarization Reconstruction Algorithm of Target Based on the Analysis of Noise in Complex Underwater Environment - Song, Qiang; Liu, Xiao; Huang, Honglian; Ti, Rufang; Sun, Xiaobing (Frontiers in Physics, 2022)
How to effectively eliminate interference such as scattering, absorption, and attenuation is a hot topic of underwater photoelectric detection at present. Around the hot issues, this paper carries out studying the method of polarization-imaging recovery in a dynamic complex underwater environment from the theory of underwater radiation transfer, and numerical simulation of imaging interference characteristics to the simulation of underwater environment experiment. First, by conducting the analysis and simulation of scattering characteristics of underwater suspension particles and bubble by using the theory of radiation transfer, and taking advantage of quantitative description on changing tendency of radiation intensity and polarization properties of light waves in turbid water under the condition of scattering interference. Second, by constructing an underwater target polarization reconstruction model on the basis of the Mueller matrix analysis, and taking target polarization characteristic into reconstruction model on the basis of classical Schechner’s model, automatically estimating polarization information of target by the method of covariance. Finally, by building a polarization imaging system in the simulated complex underwater environment that contains bubble and suspended particles, obtaining reconstructed results with different underwater environments and different materials of target. According to experiment results, and compared with other traditional methods, using the proposed method in this paper can get higher resolution and higher contrast of target in the reconstructed result.